Dupilumab for atopic dermatitis: a real-world Portuguese multicenter retrospective study. (4th July 2022) - Torres, T.; Paiva-Lopes, M. J.; Gonçalo, M.; Claro, C.; Oliveira, M.; Gomes, J.; Vieira, A. P.; Amoedo, P.; Alpalhão, M.; Nogueira, M.; Santiago, F.; Henrique, M.; et al.
Abstract: Introduction: Atopic dermatitis (AD) is a difficult-to-treat inflammatory skin disease with a high impact on patients' quality of life. Dupilumab, an IL-4 and IL-13 inhibitor, was the first monoclonal antibody approved for the treatment of moderate-to-severe AD and is currently approved in patients aged 6 or older. Methods: This is a nationwide, multicenter, retrospective, 48-week study designed by the Portuguese Group of AD to assess real-world efficacy and safety of dupilumab for the treatment of AD. Results: A total of 169 patients were enrolled, with a mean disease duration of 22.75 (±11.98) years. The percentage of patients achieving an improvement of at least 75% in Eczema Area and Severity Index (EASI) compared to baseline (EASI75 response) at weeks 12 and 48 was 67.6% and 74.1%, respectively. In the same timepoints, 25.0% and 44.1% achieved an EASI90 response. Patient-reported outcome measures also improved throughout the study period. Regarding safety, 32.0% of the patients developed adverse events, with conjunctivitis (26.6%), persistent facial erythema (4.7%), and arthritis/arthralgia (3.6%) as the more frequently reported. Conclusion: Data from real-world populations are crucial to guide clinicians in their daily decisions. This study provides data demonstrating that dupilumab is an effective and safe therapeutic option for AD.